[PP.19.24] DETERMINANTS OF INAPPROPRIATELY HIGH PULSE WAVE VELOCITY IN HYPERTENSIVE PATIENTS: A RETROSPECTIVE CROSS-SECTIONAL COHORT STUDY. (September 2017) - Bruno, R.; Di Pilla, M.; Buralli, S.; Sgrò, M.; Modesti, P.A.; Taddei, S.; Ghiadoni, L.
Abstract : Objective: Age and blood pressure (BP) are known to be the main determinants of large artery stiffness. However other factors may lead to an inappropriately high pulse wave velocity (PWV) on top of these two factors. We investigated the determinants of inappropriately high PWV in hypertensive patients, and their possible role in causing organ damage accrual. Design and method: Hypertensive patients were selected among those attending a visit in our Hypertension Outpatient Clinic and undergoing carotid-femoral PWV by applanation tonometry, and cardiac and carotid ultrasound during a 5-year period (2006–2011). Inappropriately high pulse wave velocity (PWV) was calculated as the ratio between the observed value and the values predicted according to the formula derived from international reference values stratified by age and mean BP (oPWV/pPWV). Results: 731 hypertensive patients were selected (age 30–88 years, 42% women, 57% taking BP-lowering drugs). Median oPWV/pPWV was 102% (range 61–196%). In a multiple linear regression model, independent determinants of oPWV/pPWV were: daylight hours (beta -1.72, p < 0.001), age (beta -0.73, p < 0.001), BMI (beta 0.49, p = 0.01), blood glucose (beta 0.18, p < 0.001), mean BP (beta = -0.25, p = 0.002) and heart rate (beta = 0.22, p = 0.003). Though oPWV/pPWV was significantly higher in men and current smokers, the association disappeared in the multiple regression model. There was no association between oPWV/pPWV and any BP-lowering drug class. oPWV/pPWV was not associated with left ventricular mass. Conversely, oPWV/pPWV was an independent determinant of the presence of carotid plaques (beta 7.35, 5–95%CL 2.36–12.34). Conclusions: In hypertensive patients, inappropriately elevated PWV is associated more tightly than observed PWV to younger age and high blood glucose, thus it might help to better depict vascular aging in younger hypertensives and in those with metabolic alterations. A more advanced atherosclerotic process might also contribute to excess aortic stiffness. Whether an inappropriately high PWV translates into an increased cardiovascular risk should be determined in longitudinal studies.